Can simple advice eliminate the gender gap in willingness to compete? - Dany Kessel; Johanna Mollerstrom; Roel van Veldhuizen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
As a recent literature has demonstrated, men and women differ in their willingness to sort into competitive environments. In particular, men are more willing than women to compete. We investigate whether it is possible to reduce the gender gap in willingness to compete through an information intervention that informs participants of the gap and advises them about the potential earnings implications. We find that this simple information intervention reduced the gender gap, both in a laboratory study at a German university and in a field study with Swedish high school students. Whereas some participants (primarily high performing women) benefited from the intervention, others lost out. We discuss the implications for efficiency and policy.
Keywords: C91; D91; J16; 330; Gender Differences; Competitiveness; Advice; Experiment